The ethics of photojournalism in Lithuania: views of the news photographers - Urbonavičiūtė, Laura (Žurnalistikos tyrimai, 2015)
Digital manipulation in photojournalism is the subject of ongoing debate. At the heart of the controversy over what is and what is not an acceptable alteration of a photograph is the often tenuous relationship between the reality and the captured image. Digital photography has complicated the situation because alterations are easier to accomplish and more difficult to detect. However, there is no consensus among the visual journalists about what comprises ethical image-making. This study examines some of the challenges faced by photojournalists in Lithuania, where news photography was hampered by decades of the Soviet occupation. A questionnaire of Lithuanian Press Photo Club members and two focus groups of photojournalists showed broad agreement about the acceptable alterations of the photographic image and other ethical norms but revealed a dearth of professional empowerment to put norms into practice. Photojournalists see themselves less as journalists and more as providers of a service to media organizations. Agreement about the need to regulate the professional ethics was accompanied by denials that photojournalists can take a personal responsibility for their work.